The Effect of Product Quality and Service Quality on Member Satisfaction on Multipurpose Blessing Loans at KSPPS BMT NU East Java Camplong Branch - Nisa’, Khoirun; Umam, Khotibul (Universitas Muhammadiyah Sidoarjo, 2025)
This research aims to analyze the influence of product quality and service quality on member satisfaction for the Multiguna Berkah Loan product at KSPPS BMT NU East Java, Camplong Branch. The research employed a quantitative method through multiple linear regression analysis with a sample of 98 respondents drawn from the population of members using the loan product. The results indicate that both product quality and service quality have a positive and significant impact on member satisfaction. These findings demonstrate that improvements in product and service quality can increase member satisfaction, which in turn can strengthen their loyalty to the Multiguna Berkah Loan product at KSPPS BMT NU East Java, Camplong Branch. This research provides important implications for the management of KSPPS BMT NU East Java, Camplong Branch to continuously enhance product and service quality and collect feedback from members for sustainable improvement.